Renal Transplantation Using Belatacept Without Maintenance Steroids or Calcineurin Inhibitors. Issue 5 (31st March 2014) - Kirk, A. D.; Guasch, A.; Xu, H.; Cheeseman, J.; Mead, S. I.; Ghali, A.; Mehta, A. K.; Wu, D.; Gebel, H.; Bray, R.; Horan, J.; Kean, L. S.; et al.
<x xml:space="preserve">Abstract</x> Kidney transplantation remains limited by toxicities of calcineurin inhibitors (CNIs) and steroids. Belatacept is a less toxic CNI alternative, but existing regimens rely on steroids and have higher rejection rates. Experimentally, donor bone marrow and sirolimus promote belatacept's efficacy. To investigate a belatacept‐based regimen without CNIs or steroids, we transplanted recipients of live donor kidneys using alemtuzumab induction, monthly belatacept and daily sirolimus. Patients were randomized 1:1 to receive unfractionated donor bone marrow. After 1 year, patients were allowed to wean from sirolimus. Patients were followed clinically and with surveillance biopsies. Twenty patients were transplanted, all successfully. Mean creatinine (estimated GFR) was 1.10 ± 0.07 mg/dL (89 ± 3.56 mL/min) and 1.13 ± 0.07 mg/dL (and 88 ± 3.48 mL/min) at 12 and 36 months, respectively. Excellent results were achieved irrespective of bone marrow infusion. Ten patients elected oral immunosuppressant weaning, seven of whom were maintained rejection‐free on monotherapy belatacept. Those failing to wean were successfully maintained on belatacept‐based regimens supplemented by oral immunosuppression. Seven patients declined immunosuppressant weaning and three patients were denied weaning for associated medical conditions; all remained rejection‐free. Belatacept and sirolimus effectively prevent kidney allograft rejection without CNIs or steroids when used following alemtuzumab induction. Selected, immunologically low‐risk patients can be maintained solely on once monthly intravenous belatacept.